2015
DOI: 10.1159/000373896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cumin cyminum L. Intake on Weight Loss, Metabolic Profiles and Biomarkers of Oxidative Stress in Overweight Subjects: A Randomized Double-Blind Placebo-Controlled Clinical Trial

Abstract: Background: The current study was performed to determine the effects of cumin cyminum L. intake on weight loss and metabolic profiles among overweight subjects. Methods: This randomized double-blind placebo-controlled clinical trial was conducted among 78 overweight subjects (male, n = 18; female, n = 60) aged 18-60 years old. Participants were randomly assigned into three groups to receive: (1) cumin cyminum L. capsule (n = 26); (2) orlistat120 capsule (n = 26) and (3) placebo (n = 26) three times a day for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 24 publications
3
65
1
1
Order By: Relevance
“…The result of this study indicated that green cumin has positive and significantly meaningful effect on glucose of serum and lipid profile. But in another study performed on overweight subjects, no meaningful effect of C. cyminum on plasma glucose in a fasting state and lipid profile was detected 24 . As most studies have been performed on laboratory animals,16, 25, 26, 27, 28, 29, 30 and due to lack of comparison on the rate of effectiveness of the different doses of this plant on patients with diabetes type II as well as controversial outcomes of the studies, it is essential to compare the effectiveness of the different doses of green cumin extract.…”
Section: Introductionmentioning
confidence: 89%
“…The result of this study indicated that green cumin has positive and significantly meaningful effect on glucose of serum and lipid profile. But in another study performed on overweight subjects, no meaningful effect of C. cyminum on plasma glucose in a fasting state and lipid profile was detected 24 . As most studies have been performed on laboratory animals,16, 25, 26, 27, 28, 29, 30 and due to lack of comparison on the rate of effectiveness of the different doses of this plant on patients with diabetes type II as well as controversial outcomes of the studies, it is essential to compare the effectiveness of the different doses of green cumin extract.…”
Section: Introductionmentioning
confidence: 89%
“…Dietary supplements and placebo (paraffin) capsules were produced by the department of the formulation of Barij Medicinal Plants Research Center (Barij Essence Pharmaceutical, Kashan, Iran) [12]. To produce dietary supplement hard capsules, at first green tea, capsaicin and ginger essential oil was dissolved in poly ethylene glycol 4,000 in 25°C; then it was en-coated into a capsule [12]. Analysis of green tea, capsaicin and ginger capsules was done in the laboratory of Barij Essence, Kashan, Iran by the high-performance liquid chromatography method [12].…”
Section: Methodsmentioning
confidence: 99%
“…To produce dietary supplement hard capsules, at first green tea, capsaicin and ginger essential oil was dissolved in poly ethylene glycol 4,000 in 25°C; then it was en-coated into a capsule [12]. Analysis of green tea, capsaicin and ginger capsules was done in the laboratory of Barij Essence, Kashan, Iran by the high-performance liquid chromatography method [12]. Following analysis of green tea, it was detected that the major components were polyphenols including EGCG, epicatechin gallate, epicatechins, flavanols and caffeine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of the Cuminum cyminum and orlistat120 resulted in a similar significant decrease in weight (-1.1 ± 1.2 and -0.9 ± 1.5 compared with placebo 0.2 ± 1.5 kg, respectively, p = 0.002) and BMI (-0.4 ± 0.5 and -0.4 ± 0.6 compared with placebo 0.1 ± 0.6 kg/m(2), respectively, p = 0.003). In addition, Cuminum cyminum L., compared with orlistat and placebo, led to a significant reduction in serum insulin levels (-1.4 ± 4.5 vs. 1.3 ± 3.3 and 0.3 ± 2.2 µIU/ml, respectively, p = 0.02), HOMA-B (-5.4 ± 18.9 vs. 5.8 ± 13.3 and 1.0 ± 11.0, respectively, p = 0.02) and a significant rise in QUICKI (0.01 ± 0.01 vs. -0.005 ± 0.01 and -0.004 ± 0.01, respectively, p = 0.02) [139].…”
Section: Cuminum Cyminummentioning
confidence: 96%